INSPIRASI WIRAUSAHA ALUMNI, STUDI KUNJUNGAN LAPANGAN KE USAHA YARA CAPPUCINO - Muhammad Rangga Wibiksana; Amanda Tri Utami; Muhammad Fariz Abdullah Pelu (Taksasila Edukasi Insani, 2025)
The internship activity at the Yara Cappucino micro business aims to provide students with direct experience in understanding the entrepreneurial process in practice. Through observations and interviews during three stages of visits, information was obtained about the business background, operational strategies, human resource management, and marketing and financial aspects. Yara Cappucino, which has been established for more than four years, shows the resilience of small businesses in facing challenges such as pandemics, bad weather, and limited promotion. The results of the internship show that the key to success lies in product innovation, consistent service, and strong motivation from the business owner. This activity provides real learning for students about the importance of perseverance, adaptive strategies, and the great potential of digitalization in developing UMKM in the modern era.Kata kunci : magang, UMKM, kewirausahaan, minuman kekinian, Yara Cappucino.